DEVELOPMENT OF LEAFLET BASED ON THE BRUNER THEORY ON THE MATERIALS OF THE TWO-VARIABLE LINEAR EQUATION SYSTEM - Dona Afriyani (MATEMATIKA DAN PEMBELAJARAN, 2020)
This study aims to develop a leaflet based on Bruner's theory for the two-variable linier equation system, which is valid and describes its characteristics. Research development is used to take three stages, namely the prelimanary reseach, prototipe design and assessment. The instrument in the form of a product validation sheet was designed to obtain an assessment from an expert in mathematics, mathematics education and learning media. Aspects assessed include content validity, constructs, graphics and language. Data analysis uses the percentage formula and the results obtained compared with the validity qualification criteria of a product. Furthermore, the characteristics of the leaflet are described. Validation results for all aspects are classified as very valid. Bruner's theory-based leaflets that have been declared very valid by three validators still need improvement, especially aspects of language. Based on the validator's evaluation and validator's suggestion, finally obtained the characteristics of the Bruner theory-based leaflet for valid SPLDV material namely leaflets: in accordance with the learning objectives of SPLDV, according to the characteristics needs of junior high school students, containing material presented following the stages of Bruner's theory and in accordance with the level of student understanding